Pelaksanaan Kegiatan Sunatan Massal Sebagai Upaya Peningkatan Kesehatan Reproduksi Anak Di Kecamatan Cipare - Revi Naldi; Kenny Cantika Abadi; Luluk Hermawati; Rukman Abdullah; Louisa Ivana Utami; Ekawati Rini Wulansari (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Implementation Of A Mass Circumcision Program As An Effort To Improve Children’s Reproductive Health In Cipare District. Mass circumcision is a promotive and preventive intervention that plays an important role in maintaining boys’ health, particularly in relation to reproductive health. Limited access to healthcare services and socioeconomic factors in certain regions contribute to the low coverage of early-age circumcision, thereby increasing the risk of conditions such as phimosis, balanitis, and urinary tract infections. This community service activity aimed to improve children’s health through the implementation of a mass circumcision program in Cipare District, Serang City, Banten Province. The activity involved 23 boys aged 3–8 years, with the majority of participants in the 6–8-year age group. The implementation included initial health screening, parental education, circumcision procedures performed by medical personnel, and post-procedure monitoring. The results showed that all procedures were carried out safely and effectively without serious complications. Several medical indications were identified among participants, including phimosis, balanitis, and a history of urinary tract infections. This program provided direct benefits in preventing children’s health problems and increasing parental awareness of the importance of early reproductive health. It has the potential to serve as a sustainable promotive and preventive strategy to improve children’s health status at the community level.